Boron Arylations of Subporphyrins with Aryl Zinc Reagents. Issue 10 (27th January 2016) - Kotani, Ryota; Yoshida, Kota; Tsurumaki, Eiji; Osuka, Atsuhiro
Abstract: Boron arylations of B‐ (methoxo)triphenylsubporphyrin have been developed with a combined use of ArZnI⋅LiCl and trimethylsilyl chloride. Aryl zinc reagents bearing bromo, cyano, amide, and ester groups can be employed for the B ‐arylation reaction to provide the corresponding B ‐arylated subporphyrins in moderate yields. Postmodifications of B ‐arylated subporphyrins have been demonstrated without loss of the B−C bond. These modifications include conversion of the cyano group into a benzoyl group with PhMgBr, hydrolysis of the ester group to give B ‐(4‐carboxyphenyl)subporphyrin, and Pd‐catalyzed Suzuki–Miyaura coupling of the 4‐bromophenyl group to give a 1, 4‐phenylene‐bridged subporphyrin–Zn II porphyrin hybrid that displays intramolecular excitation energy transfer from the subporphyrin to the porphyrin. The newly synthesized B ‐arylated subporphyrins have been fully characterized by NMR, UV/Vis absorption and fluorescence spectroscopies, mass spectrometry, electrochemical measurements, and X‐ray diffraction analysis. Abstract : Bonding B to C : Boron arylations of B‐ (methoxo)triphenylsubporphyrin have been developed with a combined use of ArZnI⋅LiCl and trimethylsilyl chloride (TMSCl; see scheme), which allow the synthesis of B ‐aryl subporphyrins bearing bromo, cyano, amide, and ester groups. Postmodifications of the B ‐aryl subporphyrins have been demonstrated without loss of the B−C bond. Newly synthesized B ‐arylated subporphyrins have been fully characterized.